ANALISIS KEBUTUHAN GURU MATA PELAJARAN PRODUKTIF DI INDUSTRI PENDIDIKAN MENENGAH MELALUI PEMODELAN MATEMATIKA - Taufik Hidayat; Hasbullah Hasbullah (Fakultas Teknik Universitas Tulang Bawang Lampung, 2020)
Vocational Teacher Needs in productive subject programs (Practical Teachers) have an important role in producing competent SMKs. This study aims to provide a model for the procurement of productive teacher needs. At present the need for productive subject teachers is less than 120,000 compared to the number of SMK students of more than 5,000,000 (DitPSMK, 2016). In this study using a mathematical model through the calculation of multiple linear regression models on the variable Number of SMK Students, industry needs, number of SMKs and the budget. The results of this study are a mathematical model in determining the needs of productive teachers Y = 280966 - 41.6 X1 - 12.47 X2 + 33.4 X3 - 20.7 X4. Keywords: Vocational Teacher, Multiple Linear Regression, Mathematical Modeling